Fantastic Macrofungi in Poncokusumo District, Bromo Tengger Semeru National Park (TNBTS) Area and Their Habitat Characteristics - Amelia, Aquinita Shinta Setya; Dewi, Rosita Fitrah; Setyawati, Heni; Hafazallah, Khalid; Putrie, Rahayu Fitriani Wangsa; Mubarok, Husni (Journal of Tropical Biodiversity and Biotechnology, 2024)
Bromo Tengger Semeru National Park (TNBTS) is a conservation area in East Java with an abundance of biodiversity, including macrofungi. This study aims to identify the macrofungal species existing in Poncokusumo district, TNBTS area, and their habitat characteristics for a further sustainable study of fungi. This study used a purposive sampling method by opportunistic exploration. Identification of macrofungi is conducted by morphological analysis and habitat characterization. The study identified 15 macrofungal species categorized as Ascomycota and Basidiomycota, that were distinct in their habitat characteristics. The 15 macrofungal species inhabited leaf litter, wood litter, soil, and bamboo.